Art in Everyday Life : Observations on Contemporary Canadian Design (Toronto : The Power Plant, 1988)
Ball, Douglas ; Gidman, Claude ; Kuypers, Jan ; Lamb, Thomas ; Leser, Max ; Morin, André ; Smith, Morley ; etc.
Art in Everyday Life : Observations on Contemporary Canadian Design, The Power Plant, Toronto, 24 June - 11 September 1988
English
kunstcatalogus
Keywords: Canada